ANALISIS PENGARUH PERENDAMAN LARUTAN KULIT SINGKONG (Manihot esculenta Cortex) TERHADAP KANDUNGAN LOGAM BERAT TIMBAL (Pb) DALAM KERANG DARAH (Anadara granosa) - Susanti, Maria Mita; Priamsari, Margareta Retno (Media Farmasi Indonesia, 2017)
ABSTRACKMussles blood (Anadara granosa) is a type of shell that is often consumed by Indonesian community. The shells have non selective feeder and sessile filter that relatively high which mean heavy metal content is found in the shell’s body due to the accumulation of the heavy metals. In an effort to reduce heavy metals in mussles blood, it can be done using the utilization of cassava skin waste. Cassava skin can be used as a material of reducing the heavy metal content of Pb (Lead) in mussles because it contains cellulose that can modify the group to produce hydroxyl which can bind Pb metal ions. This research aimed to analyze the effect of soaking of cassava skin solution (Manihot esculenta Cortex) with decreasing level of heavy metal lead (Pb) on mussles blood (Anadara granosa). This was an experimental research with treatment of cassava skin concentration of 1%, 1.5% and 3% and soaking time 10 minutes, 40 minutes and 80 minutes. The independent variables are concentration of cassava skin solution, soaking time and dependent variable in this research is Pb concentration in mussles blood (Anadara granosa). Samples were analyzed using an Atomic Absorption Spectrophotometer (SSA). The data were analyzed using Kendall's Tau test. The results showed that there was influence of decreasing percentage of heavy metal Pb on soaking time (p <0.05) but did not affect to concentration of cassava skin solution (p> 0.05).